Observations on the maturation of thyroid function in early fetal life - Greenberg, Arnold H. (1970)
Serum samples were obtained from 21 normal human fetuses after therapeutic abortion for psychiatric indications. Fetal crown-rump length ranged from 5.2 to 22.5 cm, corresponding to the gestational age of 65-168 days. Serum thyroxine, assayed by a modification of the Murphy-Pattee method, was identified in the second smallest fetus examined at 78 days gestation. Thereafter it increased rapidly, maintaining a significant linear correlation with crown-rump length until term (r = 0.800, P < 0.001). Free thyroxine (FT4) also increased in a linear relation to gestational age (r = 0.908, P < 0.001), but reached term levels by 18-20 wk. Radioimmunoassayable thyroid-stimulating hormone (TSH) was detected at 78 days gestation. Levels increased rapidly with advancing gestation, so that by 16 wk almost all were within the range of term infants. After 16 wk gestation, levels were usually greater than 4.0 μU/cc, higher than that seen in normal children. No correlation was demonstrated between the serum TSH levels and total thyroxine. TSH and FT4, however, increased in a parallel manner with a significant positive correlation. This suggested that fetal TSH secretion was responsive to FT4 levels from very early in gestation, possibly as early as 11 wk. Thyroxine-binding globulin (TBG) was detected in a fetus of 78 days gestation (1.4 μg/100 ml). Levels increased rapidly, paralleling the rise in serum thyroxine and maintaining a linear correlation with crownrump length (r = 0.864, P < 0.001). Thyroxine-binding prealbumin binding capacity (TBPA) in fetuses 14-24 wk gestation was comparable with that seen at term. When examining the distribution of tracer amounts of thyroxine-(131)I (T4-(131)I) between the thyroxine-binding proteins, it was found that a major fraction was bound to TBPA and albumin during the early part of gestation. This decreased linearly with maturation of the fetus as the fraction bound to TBG increased. By 20 wk gestation fetal TBG was able to bind 78% of tracer despite a TBG capacity of only 7.7 μg/100 ml. This appeared to be the result of relatively low concentrations of TBPA and albumin during this period of gestation. The theoretical association constant calculated for fetal and newborn TBG was found to be similar to that estimated for normal adult males and females.